BAUHAUS AND ITS REFLECTION ON FORMING OF THE ARTISTIC PRACTICES ON EX-YUGOSLAVIAN CULTURAL REGION - Drobnjak, Boško; Nikolić, Marko (Arhitektura i urbanizam, 2019)
The topic of this paper is formed around a group of students of the Kingdom of Serbs, Croats and Slovenians (from 1929. Kingdom of Yugoslavia) who have studied architecture, textile design, photography and the fine arts at German Bauhaus School between 1924. and 1932. Education at Bauhaus, the political moment, and the work in different prestigious architectural firms or individual design practices were extremely important for the creation of ideological frameworks of Yugoslavian Bauhaus students’ creativity. The aim of the research is to read artistic practices from the perspective of aesthetics, and the summed socio-historical context, in relation to the individual cases of Yugoslav students, to determine the cultural and social position of their artistic work. A characteristic method for the paper is taking actions within the boundaries of existing sources and interpretations of which the main subject of this topic is shaped.